NMN protects cisplatin-associated AKI via NAD+/SIRT1 pathway - Wen, Zhaozhi; Wang, Jiazeng; Yang, Yihang; Chen, Longlong; Ji, Xiangge; Liu, Dong; Shi, Chongxu (Frontiers in Immunology, 2026)
Acute kidney injury (AKI) is a critical public health concern with high morbidity and mortality. The chemotherapy agent cisplatin is widely used for various solid tumors; however, cisplatin-associated AKI (CIS-AKI) is a frequent complication in the clinic. Nicotinamide adenine dinucleotide (NAD+) is a coenzyme central to metabolism and redox reactions. β-Nicotinamide mononucleotide (NMN), a key precursor of NAD+, has shown protective effects in various disease models, but its role in CIS-AKI remains unclear. In this study, male mice subjected to CIS-AKI and cisplatin-treated HK-2 cells were employed as in vivo and in vitro models, respectively, to evaluate the renoprotective effects of NMN. Bulk RNA sequencing revealed marked inflammatory activation and disruption of NAD+ metabolism in cisplatin-treated mouse kidneys. NMN administration significantly ameliorated kidney dysfunction, as indicated by reduced plasma creatinine and blood urea nitrogen (BUN) levels, attenuated tubular injury, and decreased expression of kidney injury markers NGAL and KIM-1. It also markedly suppressed kidney inflammation, characterized by reduced IL-6 and IL-18 levels, diminished neutrophil infiltration and macrophage accumulation. Consistently, in vitro, NMN attenuated cisplatin-induced reactive oxygen species (ROS) generation and lactate dehydrogenase (LDH) release in HK-2 cells. Mechanistically, NMN elevated kidney NAD+ levels and enhanced SIRT1 expression. These findings demonstrate that NMN protects against CIS-AKI by activating the NAD+–SIRT1 pathway, thereby reducing oxidative stress and inflammation, and suggest its potential as a therapeutic strategy for CIS-AKI.